Design, preparation, and evaluation of liposomal gel formulations for treatment of acne: in vitro and in vivo studies. (4th March 2019) - Madan, Sumit; Nehate, Chetan; Barman, Tarani Kanta; Rathore, Anurag S.; Koul, Veena
Abstract: The study highlights the significance of co-application of bioactive components into liposomal gel formulations and their comparison to azithromycin for treatment of Acne. A Design of Experiments (DoE) approach was utilized to obtain optimized liposomal formulation encapsulating curcumin, with size and zeta potential of ∼100 nm and ∼14 mV, respectively, characterized by DLS, HR-TEM, FESEM, and AFM. The curcumin liposomal dispersion depicted excellent stability over the period of 60 days, which was further converted in gel form using Carbopol. Pharmacokinetics of curcumin-loaded liposomal gel showed that T max for curcumin was achieved within 1 h of post application in both stratum corneum and skin, indicating quick penetration of nano-sized liposomes. Stratum corneum depicted C max of 688.3 ng/mL and AUC0-t of 5857.5 h × ng/mL, while the skin samples displayed C max of 203.3 ng/gm and AUC0-t of 2938.1 h × ng/gm. Lauric acid and azithromycin liposomal gel formulations were prepared as per the optimum parameters obtained by DoE. In antibacterial activity using agar diffusion assay, lauric acid gel formulation revealed ∼1.5 fold improved antibacterial effect than curcumin gel formulation. Interestingly, their co-application (1:1) exhibited significantly enhanced antibacterial effect against both macrolide-sensitive (1.81 versus 1.25 folds) and resistant strains of P. acnes (2.93 versus 1.22 folds) than their individual counterparts. The in vivo studies in rat ear model displayed a ∼2 fold reduction in comedones count and cytokines (TNF-α and IL-1β) on co-application with curcumin and lauric acid liposomal gel compared to placebo treated group. Graphical Abstract: